冠動脈インターベンションを受けた虚血性心疾患患者の自己管理行動に影響する要因 - 川上 千普美; 松岡 綠; 樗木 晶子; 長家 智子; 赤司 千波; 篠原 純子; 原 頼子 (日本看護研究学会雑誌, 2006)
The purpose of this study was to elucidate the factors influencing the self-management behavior of the patients with ischemic heart disease after the coronary interventions. Especially we studied the relationship among self-management behavior, family relationship and psychological aspect. We carried out this study by mail questionnaires. Questionnaires included following factors: demographic factors, predisposing factors (anxiety, depression, and stress), enabling factors (family environment), and reinforcing factors (family support). Subjects were 131 patients (99 males) whose average age was 68.8±7.7 years old. Multiple regression analysis was performed to identify the variables that influenced self-management behavior. Family support, age, sexuality, and cohesiveness of family members were significant predictors of the self-management behavior, but anxiety, depression, and stress did not significantly influence it. However, psychological aspect and family relationship were related mutually, and thus it was suggested that psychological aspect influenced the self-management behavior indirectly. This study showed the importance of the good relationship between patients and their family members in order to maintain the self-care behavior of the patients. To establish such good relationships, we need to intervene between the patients and their family members and to educate the patients together with their family members based on their social roles and backgrounds. 本研究の目的は，冠動脈インターベンションを受けた虚血性心疾患患者の自己管理行動の影響要因を明らかにし，特に家族関係および心理的側面に焦点を当てて検討することである。郵送法による自記式質問紙調査を実施し，質問紙は自己管理行動，属性要因，前提要因（不安・抑うつ・ストレス），実現要因（家族環境），強化要因（家族サポート）で構成した。調査対象237名中，145名より回答（回収率61.1％）を得て，131名を分析対象とした。平均年齢68.8±7.7歳で，男性99名であった。重回帰分析の結果，自己管理行動の影響要因として，影響力の強い順に家族サポート，年齢，性別，家族の結びつきが明らかになった。心理的側面を示す不安・抑うつ・ストレスは，有意な変数ではなかった。しかし，自己管理行動に最も影響した家族関係と心理的側面は相互に関連し，間接的に自己管理行動に影響することが推察された。本研究の結果，患者と家族がよい関係性が保てるような環境調整，家族のサポートを得るための介入，家族を含めたセルフケア教育，および患者の社会的役割背景を考慮した教育の必要性が示唆された。